1996
DOI: 10.1177/106002809603000404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Standard-Dose Trimethoprim/Sulfamethoxazole on the Serum Potassium Concentration in Elderly Men

Abstract: Therapy with standard-dose TMP/SMX is associated with a slight increase in the serum potassium concentration. Routine monitoring of the serum potassium concentration in patients who are treated with standard-dose TMP/SMX therapy is unnecessary. However, TMP/SMX should be considered as a possible cause of unexplained hyperkalemia in elderly patients receiving TMP/SMX therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Of interest is that these were never cited reasons in the kidney transplant population. Drug‐induced nephrotoxicity (from interstitial nephritis) and hyperkalemia are well‐documented in the setting of TMP‐SMX therapy 9,26 . Reports of studies comparing TMP‐SMX to placebo for infection prophylaxis in kidney transplant recipients do not detect discernible TMP‐SMX induced renal toxicity, 22 though case reports of interstitial nephritis are rarely reported 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest is that these were never cited reasons in the kidney transplant population. Drug‐induced nephrotoxicity (from interstitial nephritis) and hyperkalemia are well‐documented in the setting of TMP‐SMX therapy 9,26 . Reports of studies comparing TMP‐SMX to placebo for infection prophylaxis in kidney transplant recipients do not detect discernible TMP‐SMX induced renal toxicity, 22 though case reports of interstitial nephritis are rarely reported 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TMP‐SMX may prevent other OIs, including Toxoplasma , Nocardia, and Listeria infections 5‐7 . Side effects attributed to TMP‐SMX including myelotoxicity, allergic reactions, rash, hyperkalemia, hepatitis, interstitial nephritis, pancreatitis, and aseptic meningitis may lead to the utilization of second line alternative prophylactic agents (APAs) such as aerosolized pentamidine, dapsone, or atovaquone 4,8‐10 . However, such TMP‐SMX side effects are unlikely when used at 1 double strength three times a week or 1 single strength daily 10‐13 .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Hyperkalaemia has also been reported in patients treated with standard doses of trimethoprim+sulfamethoxazole. [12][13][14][15] The risk of hyperkalaemia is increased if trimethoprim+ sulfamethoxazole is concurrently prescribed with drugs that can increase plasma potassium concentration. A recent study reported a major increase in the risk of hyperkalaemia-associated hospitalisation if trimethoprim+ sulfamethoxazole (as opposed to other antibiotics) was prescribed concurrently with angiotensin converting enzyme inhibitors or angiotensin receptor blockers.…”
Section: Introductionmentioning
confidence: 99%